2013
DOI: 10.4276/030802213x13603244419158
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Activity and Participation Outcomes for Children and Youth with Acquired Brain Injury: An Occupational Therapy Perspective

Abstract: Introduction: Intervention outcomes for children and youth with acquired brain injuries should be measured in terms of participation in activities. The aim of this study was to explore the occupational therapy outcome measures used with this group. Method: One cycle of an action research study, which focused specifically on occupational therapists, is reported. Ten occupational therapists working with children and youth with acquired brain injuries collated the outcome measures they used and mapped their fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Many systematic reviews of diagnostic groups have focused on measures of participation domains, commonly following the International Classification of Functioning, Disability and Health–Children and Youth (ICF-CY) domains of activity and participation, such as learning and applying knowledge, general tasks and demands, mobility, self-care and major life areas [ 30 ]. [ 19 ] reported in their systematic review that measures covered all ICF-CY domains of participation and activity for children with ABI, and that self-care in particular was covered well. The authors concluded that the occupational therapy assessments were more holistic in occupational performance, unlike medical assessments which were commonly related with bodily functions [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many systematic reviews of diagnostic groups have focused on measures of participation domains, commonly following the International Classification of Functioning, Disability and Health–Children and Youth (ICF-CY) domains of activity and participation, such as learning and applying knowledge, general tasks and demands, mobility, self-care and major life areas [ 30 ]. [ 19 ] reported in their systematic review that measures covered all ICF-CY domains of participation and activity for children with ABI, and that self-care in particular was covered well. The authors concluded that the occupational therapy assessments were more holistic in occupational performance, unlike medical assessments which were commonly related with bodily functions [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] reported in their systematic review that measures covered all ICF-CY domains of participation and activity for children with ABI, and that self-care in particular was covered well. The authors concluded that the occupational therapy assessments were more holistic in occupational performance, unlike medical assessments which were commonly related with bodily functions [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ICF-CY has been used as a foundation to consider the role of contextual factors in the rehabilitation of young people with TBI (Cicca & Threats, 2015), but to our knowledge no other study has used the ICF-CY to analyse the post-acute goals or outcomes in young people with ABI. Community and residential paediatric neurorehabilitation services in the UK have begun to analyse the rehabilitation goals of young people with ABI in order to shape the interventions provided (Dunford, Bannigan, & Wales, 2013), but further research is needed in order to develop a systematic and evidence-based approach for this. This study aimed to: Increase understanding of the community neuropsychological rehabilitation goals of young people with ABI, and how these goals map onto the ICF-CY two-level classification.Identify if there is an association between demographic and injury-related factors and the types of community neuropsychological rehabilitation goals young people with ABI have.…”
Section: Introductionmentioning
confidence: 99%
“…The UK FIM + FAM is a measure of functional ability across two domains – motor and cognitive – which was originally developed for adults with ABI. A recent mapping exercise of the UK FIM + FAM demonstrated that the items of the measure primarily map onto the ‘Activities and Participation’ domains of the International Classification of Functioning, Disability and Health: Children and Youth Version (ICF-CY) (World Health Organization, 2007), supporting its potential as an outcome measure of functional ability (Dunford et al., 2013). The UK FIM + FAM is one of the most extensively researched and used outcome measures in adult neurorehabilitation services in the UK (Skinner and Turner-Stokes, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It is valid, reliable and responsive for adults in inpatient settings (Nayar et al., 2016; Turner-Stokes and Siegert, 2013) and community settings (Wilson et al., 2009). Outcome data from this measure are currently used to influence NHS funding decisions for neurorehabilitation services across the UK (Turner-Stokes et al., 2012), including some services for children and young people with ABI (Dunford et al., 2013). Given these implications for funding and commissioning of ABI services for children and young people with ABI, it is important to establish whether the UK FIM + FAM is valid, reliable and able to capture clinical change in a younger client group.…”
Section: Introductionmentioning
confidence: 99%